Validated nomograms for non-metastatic colorectal cancer prognosis prediction: a population-based study - Cao, Yu-Dan; Sun, Hong-Wei; Li, Tian-Ci; Xie, Jia-Rui; Shi, Xin-Ran; Chen, Qian; Chen, Yue; Peng, Zi-Yang; Qiu, Quan-Peng; Niu, Nuo-Xuan; She, Jun-Jun; Li, Xiang (Frontiers in Oncology, 2025)
IntroductionThe TNM staging system has limitations in predicting prognosis for colorectal cancer (CRC). This study aimed to develop and validate a nomogram incorporating the albumin-derived neutrophil-to-lymphocyte ratio (Alb-dNLR) score, a novel nutritional and inflammatory biomarker, to provide a more accurate and personalized prognostic prediction for patients with non-metastatic CRC.MethodsThis retrospective study included a development cohort of 457 non-metastatic CRC patients who underwent radical colectomy, and an external validation cohort of 207 patients. Optimal cut-off values for continuous variables were determined by ROC curve analysis. Multivariable Cox and LASSO regression models were used to identify independent prognostic factors for cancer-specific survival (CSS) and to construct two nomograms. The performance of the nomograms was assessed by C-indexes, calibration plots, and decision curve analysis (DCA).ResultsMultivariable analysis confirmed that a high Alb-dNLR score was an independent predictor for worse cancer-specific survival (CSS) (HR = 5.536, P < 0.001) and overall survival (OS) (HR = 4.690, P < 0.001). Both nomograms, developed from Cox and LASSO models, showed superior discrimination compared to the TNM staging system alone (C-index in development cohort: (0.785, 0.767 vs. 0.680). Calibration plots and DCA confirmed the nomograms’ accuracy and clinical utility in both cohorts.ConclusionsThe Alb-dNLR score is a simple and effective independent prognostic biomarker for non-metastatic CRC. The nomograms incorporating Alb-dNLR score provide a more accurate and practical tool than the TNM system for predicting patient survival, thereby facilitating personalized clinical decision-making.